2016
DOI: 10.1016/j.triboint.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

On the thermally-induced failure of rolling element bearings

Abstract: I would also like to thank all of my colleagues in the CeRoM laboratory of Louisiana State University for their kind help and support throughout my research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…For the convenience of comparison, Reflected Sigmoidal function and Inverse Multiquadrics function are also selected as radial basis functions, and their formulas as shown in Equations (4) and (5), respectively.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…For the convenience of comparison, Reflected Sigmoidal function and Inverse Multiquadrics function are also selected as radial basis functions, and their formulas as shown in Equations (4) and (5), respectively.…”
Section: ( )mentioning
confidence: 99%
“…The evaluation basis of bearing faults includes vibration signals [3], temperature changes [4], etc., while the most important part is the study of vibration signals. Bearing defects main sources of bearing-induced vibration in the bearing components.…”
Section: Introductionmentioning
confidence: 99%
“…The tapered roller bearings suffer mainly two types of friction, viscous and boundary, under elastohydrodynamic regime of lubrication due to the high speeds and loads under which the gearbox of a manual transmission operates, 31 whereas the rib contacts are not considered within this research. For the calculation of viscous friction at each instant, equation 16is used 32…”
Section: Bearing Frictionmentioning
confidence: 99%
“…They showed that the lubricating grease was subjected to severe thermally induced degradation by the high service temperature, which consequently resulted in decrease of the lubricating capacity of the grease. Due to the decrease in the minimum oil film thickness, the lubrication form of the roller/raceway changes from fluid lubrication to boundary lubrication, and severe surface damage and wear occur on the contact surface, thus accelerating the failure of the bearing [31,32]. Jacobs et al [33] studied the effect of raising the working temperature from 30 to 60 °C on the performance of deep groove ball bearings, which shows the cone penetration of grease decreased with the increase in temperature, leading to decline of bearing performance.…”
Section: Introductionmentioning
confidence: 99%